Cosmic Microwave Background Anisotropy Measurement From Python V - Coble, K; Dodelson, S; Dragovan, M; Ganga, K; Knox, L; Kovács, J; Ratra, B; Souradeep, T (2001)
We analyze observations of the microwave sky made with the Python experiment in its fifth year of operation at the Amundsen-Scott South Pole Station in Antarctica. After modeling the noise and constructing a map, we extract the cosmic signal from the data. We simultaneously estimate the angular power spectrum in eight bands ranging from large (l ~ 40) to small (l ~ 260) angular scales, with power detected in the first six bands. There is a significant rise in the power spectrum from large to smaller (l ~ 200) scales, consistent with that expected from acoustic oscillations in the early Universe. We compare this Python V map to a map made from data taken in the third year of Python. Python III observations were made at a frequency of 90 GHz and covered a subset of the region of the sky covered by Python V observations, which were made at 40 GHz. Good agreement is obtained both visually (with a filtered version of the map) and via a likelihood ratio test.